ANESTHESIA FOR CESAREAN SECTION: CURRENT TRENDS - Sivevski, Atanas (Department of Anaesthesia and Reanimation, Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, R.N. Macedonia, 2023)
Cesarean section (C-S) is one of the most common operations in the world, with a current average rate of 21.1%, which means that one in 5 pregnant women delivers in this way. The percentage of C-S is different around the world and varies widely, from an average of 5% (sub-Saharan Africa) to 42.8% in Latin America and the Caribbean. At the global level, the trend of C-S is constantly increasing and it is estimated that by 2030, 28.5% of pregnant women in the world will be delivered with C-S. This means that even now, and even more in the future, a huge part of the population will be exposed to surgical termination of labor, which dictates that the risk of operative morbidity and mortality should be minimized, along with the possibility of other complications related to C-S. Furthermore, unlike spontaneous delivery, where there is no need for anesthesia and the presence of an anesthesiologist, the increasing number of C-Ss globally, implies that it will very likely have an impact on the workload of obstetric anesthesiologists in general, as well as their increased demand.